2018
DOI: 10.1007/jhep05(2018)063
|View full text |Cite
|
Sign up to set email alerts
|

A minimal approach to the scattering of physical massless bosons

Abstract: Abstract:Tree and loop level scattering amplitudes which involve physical massless bosons are derived directly from physical constraints such as locality, symmetry and unitarity, bypassing path integral constructions. Amplitudes can be projected onto a minimal basis of kinematic factors through linear algebra, by employing four dimensional spinor helicity methods or at its most general using projection techniques. The linear algebra analysis is closely related to amplitude relations, especially the Bern-Carras… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
35
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 23 publications
(37 citation statements)
references
References 67 publications
(116 reference statements)
1
35
0
1
Order By: Relevance
“…In order to conjugate any amplitude, we also describe the conjugation of complete spinor-chains with momenta in Eqs. (7) through (10) and (12) and (13).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In order to conjugate any amplitude, we also describe the conjugation of complete spinor-chains with momenta in Eqs. (7) through (10) and (12) and (13).…”
Section: Discussionmentioning
confidence: 99%
“…The other two particle's spinors are then contracted with each other as either square or angle brackets. Therefore, the amplitude must be a linear combination of the terms [13].…”
Section: -Body Decaysmentioning
confidence: 99%
See 1 more Smart Citation
“…Since amplitude is gauge invariant, we can expand it using a set of gauge invariant basis B α (see e.g. [27] and also [59,78] for recent general discussion):…”
Section: Gauge Invariant Basismentioning
confidence: 99%
“…It has been shown that gauge invariance is enough to completely determine scattering amplitudes and their underlying analytical structure in certain theories [1][2][3][4][5][6][7], and it has been conjectured that locality and unitarity emerge as a consequence of imposing gauge invariance [2,8]. The investigation of which principles determine scattering amplitudes is not limited to gauge theories; it has been shown that soft theorems are enough to fix tree-level scattering amplitudes in the non-linear sigma model and Dirac-Born-Infeld [9,10], and to impose strong constraints on the Lagrangians of both scalar and vector effective field theories [11][12][13].…”
Section: Introductionmentioning
confidence: 99%